2022
DOI: 10.1186/s13018-022-02940-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes between Zero-p implant and anterior cervical plate interbody fusion systems for anterior cervical decompression and fusion: a systematic review and meta-analysis of randomized controlled trials

Abstract: Purpose The clinical outcomes of using a zero-profile for anterior cervical decompression and fusion were evaluated by comparison with anterior cervical plates. Methods All of the comparative studies published in the PubMed, Cochrane Library, Medline, Web of Science, EBSOChost, and EMBASE databases as of 1 October 2021 were included. All outcomes were analysed using Review Manager 5.4. Results Seven ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…In addition, a systematic review of anterior cervical spine surgery had reported dysphagia-related occurrences of up to 5.3% [ 17 ]. There was a systematic review, and meta-analysis illustrated that ACDF with zero-profile fixation was better than anterior cervical plate fixation regarding the incidence of postoperative dysphagia (P < 0.05), which further demonstrates the robustness of our study and substantiates the distinctive benefits of Zero-P fixation in mitigating postoperative dysphagia [ 18 ]. However, an alternate review reported no significant difference in dysphagia incidence between ACDF with and without anterior plate fixation, suggesting the need for more studies to elucidate the factors influencing dysphagia [ 19 ].…”
Section: Discussionsupporting
confidence: 67%
“…In addition, a systematic review of anterior cervical spine surgery had reported dysphagia-related occurrences of up to 5.3% [ 17 ]. There was a systematic review, and meta-analysis illustrated that ACDF with zero-profile fixation was better than anterior cervical plate fixation regarding the incidence of postoperative dysphagia (P < 0.05), which further demonstrates the robustness of our study and substantiates the distinctive benefits of Zero-P fixation in mitigating postoperative dysphagia [ 18 ]. However, an alternate review reported no significant difference in dysphagia incidence between ACDF with and without anterior plate fixation, suggesting the need for more studies to elucidate the factors influencing dysphagia [ 19 ].…”
Section: Discussionsupporting
confidence: 67%
“…There was no anterior plating performed, which is common in European countries but differs from countries such as the US. One could argue that this influenced our results; however, systematic reviews and meta-analyses of studies on fusion found no clinical benefit from the use of additional plating …”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, the procedure for Z-P implantation has a reduced operation time and decreased dysphagia incidence post-operatively compared to plating [ 28 ]. The reasoning behind this is that inserting the Z-P device reduces oesophageal stimulation and thus reduces the risk of oesophageal oedema and adhesions ​[ 29 , 30 ]. As anterior plating is not routinely performed in the spinal centre in Northern Ireland, it would be unjust to comment on our experience with this particular procedure and compare it against Z-P or Cage implants.…”
Section: Discussionmentioning
confidence: 99%